The epidemiology and identification of risk factors associated with severe dengue during the 2023 dengue outbreak in Kaohsiung City, Taiwan - Li-Teh Liu; Shi-Ya Huang; Chen-Hsuan Lin; Chun-Hong Chen; Ching-Yi Tsai; Ping-Chang Lin; Jih-Jin Tsai (Travel Medicine and Infectious Disease)
After the previous major dengue fever (DF) outbreaks in 2014 and 2015 in Taiwan, the second-largest DF outbreak re-emerged in 2023. A total of 178 patients with laboratory-confirmed dengue virus (DENV) infection, including 92 DENV-1 and 86 DENV-2 cases, were enrolled in this study conducted during the 2023 dengue outbreak in Kaohsiung City, Taiwan. This study aimed to analyze epidemiological characteristics, clinical severity, and risk factors for severe dengue (SD), as well as the diagnostic implications of the non-structural protein 1 (NS1) antigen rapid test. Patients infected with DENV-2 exhibited significantly older age, higher incidence of secondary infections, diabetes mellitus (DM), hypertension (HT), and longer hospital stays than patients infected with DENV-1. Multivariate analysis revealed that older age (age ≥65), secondary dengue infection, DM, and HT were significant independent predictors of SD. Compared with non-SD cases, SD patients were significantly more likely to be older (age ≥65), to exhibit a higher incidence of secondary infections and a greater prevalence of chronic diseases, including DM and HT. Notably, dengue-confirmed patients with negative NS1 results had a shorter duration since symptom onset (p < 0.001). Our DENV-1 and DENV-2 isolates are related to strains from neighboring Asian countries. Our findings emphasize the important factors of old age, secondary infections, and chronic diseases that contributed to dengue severity. We should meticulously manage these high-risk groups to prevent dengue progression. Screening incoming travelers for DF during the epidemic season will be an important measure to prevent the introduction of DENV into Taiwan.